2007
DOI: 10.1007/s10278-007-9076-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Radiologists’ Search Strategies for Lung Nodule Detection: Slice-Based Versus Volumetric Displays

Abstract: The goal of this study was to assess whether radiologists' search paths for lung nodule detection in chest computed tomography (CT) between different rendering and display schemes have reliable properties that can be exploited as an indicator of ergonomic efficiency for the purpose of comparing different display paradigms. Eight radiologists retrospectively viewed 30 lung cancer screening CT exams, containing a total of 91 nodules, in each of three display modes [i.e., slice-by-slice, orthogonal maximum intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…In an earlier work 14 , we showed that radiologists and laypersons had similar interaction performance when expert knowledge was not required, so we hypothesized that we could use naïve laypersons to evaluate different image navigation techniques, with results that would generalize to radiologists performing clinical tasks. For example, we had observed a lot of forward and backward scrolling during a radiology look-alike task with naïve students as subjects 9 and backward and forward scrolling in stack mode by radiologists has been similarly noted by others [11][12][13] . As a final, tertiary, issue, we were interested whether a group of naïve students would have similar performance and preferences to radiologists for the three techniques.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…In an earlier work 14 , we showed that radiologists and laypersons had similar interaction performance when expert knowledge was not required, so we hypothesized that we could use naïve laypersons to evaluate different image navigation techniques, with results that would generalize to radiologists performing clinical tasks. For example, we had observed a lot of forward and backward scrolling during a radiology look-alike task with naïve students as subjects 9 and backward and forward scrolling in stack mode by radiologists has been similarly noted by others [11][12][13] . As a final, tertiary, issue, we were interested whether a group of naïve students would have similar performance and preferences to radiologists for the three techniques.…”
mentioning
confidence: 64%
“…Wang et al 11 compared three display techniques: a stereoscopic display, slice-by-slice, and maximum intensity projections (MIP), for detecting lung nodules from CT lung volumes. They found that the stereoscopic display provided higher detection and classification performance with less interpretation time but the differences were not statistically significant in their study of eight radiologists viewing a total of 91 anomalies.…”
mentioning
confidence: 99%
“…Viewing transverse sections on a cine display results in the detection of 31% more nodules 5 mm when compared to film-based review (42). With the advent of image review stations that allow real-time reformation and rendering of transverse sections, an innumerable range of approaches are possible for navigating and evaluating the rich volumetric lung CT data (43) which impact radiologists’ effectiveness and efficiency of search (44). …”
Section: Image Based Methods For Performance Improvementmentioning
confidence: 99%
“…Then, the CAD scheme uses the (x, y) coordinate of the detected cell center and cell boundary in the ROI to define a volume of interest (VOI) in another image stack that records the FISH-probed chromosome signals. All FISH-probed signal spots recorded in the multiple image slices (in z direction) are mapped into cell ROI using a maximum intensity projection (MIP) method that enables to map a stack of 3-D image slices into one 2-D projection image [32]. Figure 4 illustrates an example of region of interests (ROIs) containing FISH signal spots captured in green spectrum in 9 focal planes (Fig.…”
Section: A Computerized Schemementioning
confidence: 99%